3-Dimensional general ADT modeling and analysis: Considering epistemic uncertainties in unit, time and stress dimension. (September 2022) - Li, Xiao-Yang; Chen, Da-Yu; Wu, Ji-Peng; Kang, Rui
Highlights: A general ADT modeling framework considering uncertainties are presented. A 3-Dimensional ADT model and a practical application procedure are developed. A bidirectional Liu process is utilized to describe the epistemic uncertainty. A new statistical method is presented for parameter estimations. Cases show the accuracy and practicability of the proposed model and framework. Abstract: Accelerated degradation testing (ADT) has been widely used to identify the performance degradation law so as to evaluate the reliability and lifetime. During this process, there are aleatory and epistemic uncertainties in the unit, time and stress dimension. However, the current studies do not have a comprehensive modeling framework and a general ADT model that fully considers and properly quantifies all sources and types of uncertainties. Aiming at these problems, this paper proposes a 3-Dimesional modeling framework and a general ADT model, and gives a new uncertain ADT model considering epistemic uncertainties in the unit, and stress dimension. Furthermore, considering the weights of observed degradation data under different stress levels, this paper proposes a new parameter estimation method, uncertain weighted least squares, to well predict degradation law and control uncertainties. Finally, a microwave case, a rubber seal case and two simulation cases are conducted to show the practicability of the proposed framework and model. The results show that the proposed framework can guide the construction of different models according to different situations; and compared with current methods, the proposed model are more appropriate for performing ADT model and quantifying uncertainties when uncertainty in the stress dimension cannot be ignored.